ANALISIS PERGERAKAN ARUS LALU LINTAS DIKAWASAN PASAR ALOK MAUMERE KABUPATEN SIKKA - Apolonarius Minggu; Yono Putra (Program Studi Teknik Sipil, 2024)
Transportation represents a derived demand resulting from various economic, social, and cultural activities. Among the urban activities that significantly influence transportation is trade and service activities. The Alok Market in Maumere has designated parking areas; however, these spaces have not been utilized optimally, as some vendors and customers continue to park their vehicles improperly. This situation leads to disorder for both drivers and pedestrians. The objective of this research was to analyze traffic flow and propose solutions to improve traffic movement within the Alok Market area. The necessary data for this study included primary data on traffic volume, side obstructions, and road geometry. This research employed a quantitative descriptive method. The analysis indicated that traffic engineering interventions are essential for regulating movement within the Alok Market. Proposed traffic management solutions includes the addition of traffic signs and direct supervision by authorized personnel to ensure the successful implementation of the traffic engineering measures designed